2020
DOI: 10.1088/1755-1315/613/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid analysis of a semi-finished meat-containing product for gerodietic nutrition

Abstract: In the gerodietic nutrition production technology there are a lot of questions that today remain unanswered. The development of recipe compositions that are fully balanced in terms of amino acids, macro- and microelements and vitamins based solely on the internal reserves of raw materials is a difficult task. As a result of our research we suggest the cutlet recipe with vitamins for gerodietic nutrition. The recipe composition includes chickpea flour, vegetables and amino acid additives - Amur grape seed flour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Depending on body weight, age and level of physical activity in 61-74 years, it is 1800-2100 kcal/day for men, 1600-2000 for women; after 75 years, 1600-1900 kcal/day for men, 1400-1700 for women [20]. Excessive consumption of food for people of older age groups can be dangerous because of the risk of obesity, varicose veins, type II diabetes mellitus, atherosclerosis, bile and urolithiasis, coronary heart disease, heart attack [15,[21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on body weight, age and level of physical activity in 61-74 years, it is 1800-2100 kcal/day for men, 1600-2000 for women; after 75 years, 1600-1900 kcal/day for men, 1400-1700 for women [20]. Excessive consumption of food for people of older age groups can be dangerous because of the risk of obesity, varicose veins, type II diabetes mellitus, atherosclerosis, bile and urolithiasis, coronary heart disease, heart attack [15,[21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the analysis and generalization of scientific literature and experimental data it was found that the optimal daily doses of vitamins consumed by elderly, senile and long-lived people, mg: retinol-0.9-1.1, thiamine -1.5-1.7, riboflavin -1.5-2.0, niacin -13.0-20.0, pantothenic acid -5.0, pyridoxine -2.0-3.5, ascorbic acid -90-110, tocopherol -15-25; mcg: biotin -50, folic acid -230-400, cyancobalamin -3, calciferol -2,5-15, phylloquinone -120 [7; 21-23]. The recommended daily norms for the use of mineral elements are also systematized, mg: potassium -2500, sodium -1300, calcium -800-1200, phosphorus-800-1200, magnesium-400-500, iron-10-18, zinc -12-15, fluorine -0.75-4, magnesium-2, copper-1; mcg: iodine-150, molybdenum-70, selenium -50-70, chromium-50 [24][25][26].…”
Section: Recommendedmentioning
confidence: 99%